Enhanced TiO2 surface electrochemistry with carbonised layer-by-layer cellulose-PDDA composite films. - Vuorema, A; Shariki, S; Sillanpää, M; Thielemans, W; Nelson, G; Foord, J; Dale, SE; Bending, S; Marken, F (2011)
In this report we demonstrate a versatile (and potentially low-cost) cellulose nano-whisker-based surface carbonisation method that allows well-defined films of TiO(2) nanoparticles surface-modified with carbon to be obtained. In a layer-by-layer electrostatic deposition process based on TiO(2) nanoparticles, cellulose nano-whiskers, and poly(diallyl-dimethylammonium) or PDDA are employed to control the ratio of surface carbon to TiO(2). Characterisation based on optical, AFM, XRD, and XPS methods is reported. Electrochemical measurements suggest improved access to surface states, dopamine binding at the anatase surface, and surface redox cycling aided by the thin amorphous carbon film in mesoporous TiO(2). In future, the amorphous carbon layer method could be applied for surface processes for a wider range of semiconductor or insulator surfaces.